APLIKASI STARTER KULTUR MURNI PADA PEMBUATAN DURIAN FERMENTASI - Hasanuddin Hasanuddin (Jurnal Agroindustri, 2011)
This study looks into the effect of pure culture starters isolated from tempoyak on fermented durian (Durio zibethinus) and its acceptability. The use of 5% pure culture starters and mixed cultures of Pediococcus acidilactici, Lactobacillus plantarum, Lactobacillus curvatus Leuconostoc mesentroides and Staphylococcus saprophyticus were analyzed in terms of acceptabilty by sensory panelists. Statistical analysis shows a significant difference among  fermented durian  with pure culture and mixed culture starters for attributes of texture and viscosity, aroma and flavor, acidity and general acceptability.